Hypotonic swelling promotes nitric oxide release in cardiac ventricular myocytes: Impact on swelling-induced negative inotropic effect - Gonano, Luis Alberto (2014)
Aims Cardiomyocyte swelling occurs in multiple pathological situations and has been associated with contractile dysfunction, cell death, and enhanced propensity to arrhythmias.We investigate whether hypotonic swelling promotes nitric oxide (NO) release in cardiomyocytes, and whether it impacts on swelling-induced contractile dysfunction. Methods and results Superfusing rat cardiomyocytes with a hypotonic solution (HS; 217 mOsm), increased cell volume, reduced myocyte contraction and Ca2+ transient, and increased NO-sensitive 4-amino-5-methylamino-2', 7'-difluorofluorescein diacetate (DAF-FM) fluorescence. When cells were exposed to HS + 2.5 mMof theNOsynthase inhibitor L-NAME, cell swelling occurred in the absence of NOrelease. Swelling-induced NO release was also prevented by the nitric oxide synthase 1 (NOS1) inhibitor, nitroguanidine, and significantly reduced in NOS1 knockout mice. Additionally, colchicine (inhibitor of microtubule polymerization) prevented the increase in DAF-FM fluorescence induced by HS, indicating that microtubule integrity is necessary for swelling-inducedNOrelease. The swelling-induced negative inotropic effectwas exacerbated in the presence of either L-NAME, nitroguandine, the guanylate cyclase inhibitor, ODQ, or the PKG inhibitor, KT5823, suggesting that NOS1-derived NO provides contractile support via a cGMP/PKG-dependent mechanism. Indeed, ODQ reduced Ca2+ wave velocity and both ODQ and KT5823 reduced the HS-induced increment in ryanodine receptor (RyR2, Ser2808) phosphorylation, suggesting that in this context, cGMP/PKG may contribute to preserve contractile function by enhancing sarcoplasmic reticulum Ca2+ release. Conclusions Our findings suggest a novel mechanism for NO release in cardiomyocytes with putative pathophysiological relevance determined, at least in part, by its capability to reduce the extent of contractile dysfunction associated with hypotonic swelling.